Między mikro-i makrohistorią. Losy Zofii F., mieszkanki Wysowej (pow. gorlicki) w okresie II wojny światowej - Syrnyk, Jarosław (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
The fates of ordinary people during war are often weaved into some kind of metastory. There are important because they constitute a part of the metastory. In the present study, based on archive material – protocols written by one of the members of so called Security Service of OUN-B, which operated in Poland until the fall of 1947 – a different approach has been adopted. The war events are a background to an attempt of an analysis of a story of a young woman from the village of Wysowa (Gorlice county). It is a story in several acts, a long story, in which we follow the protagonist to the places where she worked during the war and the tracks of her homecoming, through Czech Republic, Romania and Soviet Union – but also a shorter story of her interrogation, with a tragic, as can be assumed, finale for Zofia F
Keywords: microhistory; World War II; Poland; Ukraine; OUN (Organization of Ukrainian Nationalists); NKWD